Heat-conducting gel gasket as well as preparation method and application thereof

Through specific formulas and process processing, low-density, high resilience and high thermal conductivity thermal gel gaskets were prepared, which solved the problems of failure of thermal conductivity, high density and poor resilience of existing thermal gel gaskets under high thermal conditions, and achieved stable and efficient thermal conductivity in high-heat environments such as new energy vehicles.

CN119529542APending Publication Date: 2025-02-28SHENZHEN DEYIMENG ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411875746.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing thermal gel gaskets can easily cause gaps between the heating components and the radiator under high heat conditions, resulting in failure of thermal conductivity, and high density and poor rebound, making it difficult to meet the needs of lightweight and high rebound.

Method used

Base oil is prepared using vinyl silicone oil, vinyl silicone resin, vapor-phase silica, hexamethyldisilazane and water, and combined with inorganic material powders, powder treatment agents, platinum catalysts, modifiers and inhibitors to prepare low-density, high resilience and high thermal conductivity thermal gel gaskets through specific formulations and processes.

Benefits of technology

It realizes the low density, low compression permanent deformation rate and high resilience of thermal gel gaskets, can be used stably for a long time, and has excellent mechanical properties and high thermal conductivity. It is suitable for high-thermal environments such as new energy vehicles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005196824850000091
    Figure BDA0005196824850000091
  • Figure BDA0005196824850000101
    Figure BDA0005196824850000101
Patent Text Reader

Abstract

The invention discloses a heat-conducting gel gasket and a preparation method and application thereof, and the heat-conducting gel gasket comprises the following components in parts by weight: base oil: 98-102 parts of vinyl silicone oil, 5-20 parts of vinyl silicone resin, 15-50 parts of fumed silica, 8-25 parts of hexamethyldisilazane and 5-15 parts of water; the component A comprises 98-102 parts of base oil, 200-450 parts of inorganic material powder, 0.25-1.5 parts of a powder treating agent, 0.1-1.0 part of a platinum catalyst and 0.5-2.0 parts of a modifier, the component B comprises 98-102 parts of base oil, 200-450 parts of inorganic material powder, 0.25-1.5 parts of a powder treating agent, 1-12 parts of a cross-linking agent and 0.01-0.1 part of an inhibitor, and the mass ratio of the component A to the component B is 1: (0.8-1.2). The heat-conducting gel gasket has high resilience, high heat conductivity and low density, and can be stably applied to the field of heat conduction for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal interface materials, and in particular to a thermally conductive gel pad and a preparation method and application thereof. Background Art

[0002] Thermal interface material is a material applied between heat dissipation devices and heating devices to reduce the contact thermal resistance between them.

[0003] At present, the commonly used thermal interface materials are mainly thermal grease, thermal silicone gasket, thermal gel, etc. Thermal gel has an amorphous state and can fill the heat conduction of any gap that thermal silicone gasket cannot meet. And due to the characteristics of mild cross-linking, thermal gel will not become dry or brittle during use. Ordinary two-component thermal gel products have poor or no resilience and high density. Not only can they not meet the lightweight requirements, but they will also cause damage to accessories due to excessive internal compressive stress during initial use. After long-term use, gaps will appear between the heating components and the radiator, resulting in failure of thermal conductivity and loss of component function due to high temperature accumulation.

[0004] Therefore, there is an urgent need to develop a thermally conductive gel gasket that is lightweight and has high resilience to meet the lightweight requirements of the thermally conductive gel gasket and ensure the normal and stable use of the thermal interface material under high heat conditions. Summary of the invention

[0005] In view of the defects in the prior art, the present invention proposes a thermally conductive gel gasket and a preparation method and application thereof. The thermally conductive gel gasket provided by the present invention has low compression permanent deformation and low density, and can meet the high requirements of current electronic equipment for thermal interface materials.

[0006] The present invention provides a thermally conductive gel pad, which comprises the following components in parts by weight:

[0007] Base oil: vinyl silicone oil 98-102 parts, such as 98, 99, 100 parts, vinyl silicone resin 5-20 parts, such as 5, 10, 15, 20 parts, fumed silica 15-50 parts, such as 15, 20, 25, 30, 35, 40, 45, 50 parts, preferably 30-45 parts, hexamethyldisilazane 8-25 parts, such as 8, 10, 12, 15, 18, 20, 22, 25 parts, water 5-15 parts, such as 5, 10, 15 parts;

[0008] Component A: base oil 98-102 parts, such as 98, 99, 100, 101, 102 parts, inorganic material powder 200-450 parts, such as 200, 250, 300, 350, 400, 450 parts, preferably 250-400 parts, powder treatment agent 0.25-1.5 parts, such as 0.25, 0.5, 0.75, 1, 1.25, 1.5 parts, preferably 0.5-1.5 parts, platinum catalyst 0.1-1.0 parts, such as 0.1, 0.2, 0.4, 0.6, 0.8, 1.0 parts, preferably 0.2-0.5 parts, modifier 0.5-2.0 parts, such as 0.5, 0.8, 1, 1.5, 2 parts, preferably 0.5-1 parts;

[0009] Component B: base oil 98-102 parts, such as 98, 99, 100, 101, 102 parts, inorganic material powder 200-450 parts, such as 200, 250, 300, 350, 400, 450 parts, preferably 250-400 parts, powder treatment agent 0.25-1.5 parts, such as 0.25, 0.5, 0.75, 1, 1.25, 1.5 parts, preferably 0.5-1.5 parts, cross-linking agent 1-12 parts, such as 1, 2, 4, 6, 8, 10, 12 parts, preferably 7-12 parts, inhibitor 0.01-0.1 parts, such as 0.01, 0.02, 0.04, 0.06, 0.08, 0.1 parts, preferably 0.05-0.1 parts;

[0010] The mass ratio of component A to component B is 1:(0.8-1.2). Adding too much component A will make the gel gasket softer and increase the compression permanent deformation. Adding too much component B will make the gel gasket harder, increase the compression stress, and be easy to break.

[0011] The base oil prepared from vinyl silicone oil, vinyl silicone resin, fumed silica, hexamethyldisilazane and distilled water can make the thermally conductive gel gasket have good mechanical properties. It is premixed by heating with inorganic material powder and powder treatment agent, and hydrogen-containing silicone oil is used as a cross-linking agent. Under the action of a platinum catalyst and a modifier, an inhibitor is used to control the reaction rate, thereby improving the overall performance of the thermally conductive gel gasket.

[0012] The base oil of the specific formula of the present invention has low viscosity and good viscoelasticity. The two-component liquid silicone rubber is prepared by the base oil. The gel gasket prepared by mixing in a specific ratio has lower density and compression permanent deformation rate, and has excellent film-forming properties similar to ordinary thermal conductive gaskets, and also has a gap-filling function that ordinary thermal conductive gaskets do not have; and after the base oil is pre-processed at high temperature according to the formula, the vinyl silicone oil mixture can be given a more stable molecular structure, showing better mechanical properties.

[0013] Furthermore, the vinyl silicone oil is any one of terminal vinyl polydimethylsiloxane or side chain vinyl polydimethylsiloxane, and the vinyl content is 0.5%-1.5%.

[0014] Furthermore, the viscosity of the vinyl silicone oil is 50-500mPa·s, such as 50, 100, 110, 150, 200, 250, 300, 350, 400, 450, 500mPa·s, preferably 110-500mPa·s; if the viscosity is too high, for example, 1000mPa·s and above, the viscosity of the obtained base oil will be too high, affecting the powder addition and processing process of components A and B and affecting the mixing of various additives during the base oil production process, which is not conducive to improving the overall performance of the thermal conductive gasket.

[0015] Furthermore, the vinyl silicone resin is a vinyl MQ silicone resin with a vinyl content of 0.1%-2%, such as 0.1%, 0.2%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, preferably 0.5%-2%.

[0016] Furthermore, the inorganic material powder is at least one of zinc oxide with a particle size of 0.1-5μm, aluminum oxide with a particle size of 1-150μm, aluminum hydroxide with a particle size of 1-100μm, aluminum nitride with a particle size of 10-120μm, or boron nitride with a particle size of 10-200μm, and preferably two or more. The thermal conductivity can be improved by grading the inorganic material powder.

[0017] Furthermore, the powder treating agent is any one of 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane or hexadecyltrioxymethylsilane; by adding the powder treating agent, wet coupling treatment of the powder can be achieved, so that the powder surface activity is higher, the compatibility with the base oil is better, the thermal conductivity is higher, the thermal resistance is lower, the viscosity is lower, and the extrusion rate is higher, thereby promoting the gel gasket to have a lower compression permanent deformation and better resilience.

[0018] Furthermore, the modifier is any one of benzoyl peroxide and di-tert-butyl peroxide; the modifier of the present invention can also promote multiple cross-linking reactions to generate more short-chain silicone polymers, which can maintain the low hardness of the gel gasket while having a lower compression permanent deformation, and at the same time have excellent resilience, and also have a significant effect in improving the heat resistance and compression permanent deformation resistance of the material.

[0019] Furthermore, the crosslinking agent is at least one of a side chain hydrogen-containing silicone oil with a hydrogen content of 0.05%-0.5% or a terminal hydrogen-containing silicone oil with a hydrogen content of 0.05%-0.3%.

[0020] Furthermore, the inhibitor is any one of phenylbutynol, methylbutynol or ethynylcyclohexanol.

[0021] The present invention also provides a method for preparing the thermally conductive gel pad, comprising the following steps:

[0022] S1. Preparation of base oil: Weigh the components of the base oil formulation in parts by weight, and heat treat in vacuum at 95-160 ℃ for 1.5-8 hours to obtain a base oil;

[0023] S2. Preparation of component A: Weigh the base oil and inorganic material powder in step S1 in parts by weight, heat treat at 95-125 ° C while vacuum kneading for 0.5-2 hours, add the powder treatment agent when cooled to 65-85 ° C, stir for 1-2 hours, add the platinum catalyst and modifier after cooling and stir for 15-30 minutes to obtain component A;

[0024] S3. Preparation of component B: Weigh the base oil in step S1 in parts by weight, add the inorganic material powder, heat treat at 95°C-125°C while vacuum kneading for 0.5-2 hours, add the powder treatment agent when cooled to 65°C-85°C, stir for 1-2 hours, add the crosslinking agent and inhibitor after cooling and stir for 15-30 minutes to obtain component B;

[0025] S4. Prepare a thermally conductive gel gasket: mix component A and component B according to a mass ratio, and cure at room temperature or at 90° C.-150° C. for 10-30 minutes to obtain a thermally conductive gel gasket.

[0026] The present invention also provides the application of the thermally conductive gel pad in new energy vehicles, especially in new energy vehicle batteries; first, the thermally conductive gel pad of the present invention is lightweight, so that the thermally conductive gel pad can reduce the overall weight of new energy vehicles while maintaining efficient thermal conductivity, thereby improving energy efficiency and cruising range; secondly, the high strength and high resilience of the thermally conductive gel pad of the present invention enable the material to quickly restore its original size after being stretched or compressed when the external force is removed, thereby ensuring stability and reliability for long-term use, being able to adapt to high-frequency vibration and impact of new energy vehicles during driving, and maintaining a stable heat dissipation effect; and the thermally conductive gel pad of the present invention has high thermal conductivity, can effectively transfer the heat generated by new energy vehicle batteries and motors, ensures that they operate within the optimal operating temperature range, and improves battery life and safety. The thermally conductive gel pad of the present invention makes up for the defects of ordinary two-component thermally conductive gel products, such as poor resilience, high density, difficulty in maintaining stability, easy deformation, and reduced thermal conductivity, and can be widely used in new energy vehicles.

[0027] In summary, compared with the prior art, the present invention achieves the following technical effects:

[0028] (1) The thermally conductive gel gasket provided by the present invention has high resilience and low compression permanent deformation rate, and can be used stably for a long time;

[0029] (2) The thermally conductive gel pad provided by the present invention has high thermal conductivity;

[0030] (3) The thermally conductive gel pad provided by the present invention also has the characteristic of low density, which can meet the requirements of lightweight;

[0031] (4) The thermally conductive gel gasket provided by the present invention can also fill the gap, and the gap thickness can be as low as 0.1 mm;

[0032] (5) The thermally conductive gel pad provided by the present invention also has excellent mechanical properties. DETAILED DESCRIPTION

[0033] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Example

[0035] The present invention is further described below in conjunction with specific examples and comparative examples. The following specific examples are all preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the following examples, and are particularly not limited to the types of the various component raw materials used in the following specific examples.

[0036] 1. The sources of raw materials for the embodiments and comparative examples are as follows:

[0037] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present invention are commercially available.

[0038] 2. Various performance test methods

[0039] (1) Thermal conductivity test: refer to ASTM D5470-2017 Standard test method for thermal conductivity of thermally conductive electrical insulating materials to measure the thermal conductivity of the thermally conductive gel gasket;

[0040] (2) Density test: refer to standard GB / T 13354-1992 Liquid adhesive density determination method gravimetric cup method;

[0041] (3) Hardness test: Tested in accordance with ASTM D2240-2015 Standard Test Methods for Rubber Properties;

[0042] (4) Compression set test: Tested according to ASTM D395-2018 Standard Test Method for Compression Set Properties of Rubber;

[0043] (5) Mechanical properties test: The test was conducted according to GB / T 7757-2009 Standard test method for determination of compressive stress-strain properties of vulcanized rubber or thermoplastic rubber.

[0044] Example 1

[0045] S1. Preparation of base oil: 100 parts of vinyl-terminated silicone oil having a viscosity of 500 mPa·s and a vinyl content of 0.42%, 8 parts of vinyl MQ silicone resin having a vinyl content of 1%, 35 parts of fumed silica, 10 parts of hexamethyldisilazane and 5 parts of water were heat treated at 150°C under vacuum for 4 hours and cooled to room temperature to obtain a base oil;

[0046] S2. Preparation of component A: 100 parts of base oil and 280 parts of inorganic material powder were heat treated at 100 ° C while vacuum kneading for 2 hours, and 0.8 parts of decyltrimethoxysilane were added when cooled to 75 ° C, stirred for 1.5 hours, and after cooling, 0.3 parts of platinum catalyst and 0.5 parts of di-tert-butyl peroxide were added and stirred for 20 minutes, and cooled to room temperature to obtain component A;

[0047] S3. Preparation of component B: 100 parts of base oil, 280 parts of inorganic material powder, heat treated at 100 ° C while vacuum kneading for 2 hours, cooled to 75 ° C, added 0.8 parts of decyltrimethoxysilane, stirred for 1.5 hours, cooled, added 4 parts of a side chain hydrogen-containing silicone oil having a hydrogen content of 0.1%, 5 parts of a terminal hydrogen-containing silicone oil having a hydrogen content of 0.2% and 0.1 parts of ethynyl cyclohexanol, stirred for 20 minutes to obtain component B;

[0048] S4. Prepare a thermally conductive gel gasket: evenly mix 100 parts of component A and 100 parts of component B, and cure at 110° C. for 15 minutes to obtain a thermally conductive gel gasket.

[0049] Example 2

[0050] S1. Preparation of base oil: 100 parts of vinyl-terminated silicone oil having a viscosity of 350 mPa·s and a vinyl content of 0.5%, 10 parts of vinyl MQ silicone resin having a vinyl content of 2%, 30 parts of fumed silica, 10 parts of hexamethyldisilazane and 5 parts of water were heat treated at 140°C in vacuum for 6 hours and cooled to room temperature to obtain a base oil;

[0051] S2. Preparation of component A: 100 parts of base oil, 400 parts of inorganic material powder, heat treated at 110 ° C while vacuum kneading for 1.5 hours, cooled to 80 ° C, 1.2 parts of 8-methacryloyloxyoctyl trimethoxysilane were added, stirred for 1.5 hours, cooled, added 0.4 parts of platinum catalyst and 0.8 parts of di-tert-butyl peroxide, stirred for 20 minutes, and cooled to room temperature to obtain component A;

[0052] S3. Preparation of component B: 100 parts of base oil, 400 parts of inorganic material powder, heat treated at 110 ° C while vacuum kneading for 1.5 hours, cooled to 80 ° C, 1.2 parts of 8-methacryloyloxyoctyl trimethoxysilane were added, stirred for 1.5 hours, and after cooling, 3 parts of a side chain hydrogen-containing silicone oil having a hydrogen content of 0.18%, 6 parts of a terminal hydrogen-containing silicone oil having a hydrogen content of 0.2% and 0.08 parts of phenyl butynol were stirred for 20 minutes to obtain component B;

[0053] S4. Prepare a thermally conductive gel gasket: mix 100 parts of component A and 100 parts of component B evenly, and cure at 120° C. for 15 minutes to obtain a thermally conductive gel gasket.

[0054] Example 3

[0055] S1. Preparation of base oil: 100 parts of vinyl-terminated silicone oil having a viscosity of 200 mPa·s and a vinyl content of 0.7%, 20 parts of vinyl MQ silicone resin having a vinyl content of 0.5%, 40 parts of fumed silica, 20 parts of hexamethyldisilazane and 10 parts of water were heat treated at 130°C under vacuum for 5 hours and cooled to room temperature to obtain a base oil;

[0056] S2. Preparation of component A: 100 parts of base oil, 350 parts of inorganic material powder, heat treated at 120 ° C while vacuum kneading for 1 hour, cooled to 85 ° C, 1.4 parts of dodecyltrimethoxysilane were added, stirred for 1.5 hours, and after cooling, 0.25 parts of platinum catalyst and 1.0 parts of benzoyl peroxide were added and stirred for 20 minutes, and cooled to room temperature to obtain component A;

[0057] S3. Preparation of component B: 100 parts of base oil, 350 parts of inorganic material powder, heat treated at 120 ° C while vacuum kneading for 1 hour, cooled to 85 ° C, 1.4 parts of dodecyltrimethoxysilane were added, stirred for 1.5 hours, and after cooling, 4 parts of a side chain hydrogen-containing silicone oil having a hydrogen content of 0.18%, 8 parts of a terminal hydrogen-containing silicone oil having a hydrogen content of 0.2% and 0.05 parts of phenylbutynol were added and stirred for 20 minutes to obtain component B;

[0058] S4. Prepare a thermally conductive gel gasket: mix 100 parts of component A and 100 parts of component B evenly, and cure at 130° C. for 15 minutes to obtain a thermally conductive gel gasket.

[0059] Example 4

[0060] S1. Preparation of base oil: 100 parts of vinyl-terminated silicone oil having a viscosity of 110 mPa·s and a vinyl content of 1.0%, 20 parts of vinyl MQ silicone resin having a vinyl content of 2%, 45 parts of fumed silica, 25 parts of hexamethyldisilazane and 10 parts of water were heat treated at 130°C under vacuum for 4 hours and cooled to room temperature to obtain a base oil;

[0061] S2. Preparation of component A: 100 parts of base oil and 400 parts of inorganic material powder were heat treated at 110 ° C while vacuum kneading for 1.5 hours, and 1.5 parts of hexadecyltrioxymethylsilane were added when cooled to 80 ° C, stirred for 1.5 hours, and after cooling, 0.5 parts of platinum catalyst and 0.8 parts of benzoyl peroxide were added and stirred for 20 minutes, and cooled to room temperature to obtain component A;

[0062] S3. Preparation of component B: 100 parts of base oil and 400 parts of inorganic material powder were heat treated at 110 ° C while vacuum kneading for 1.5 hours, cooled to 80 ° C, 1.5 parts of hexadecyl trioxymethyl silane were added, stirred for 1.5 hours, and after cooling, 2 parts of a side chain hydrogen-containing silicone oil having a hydrogen content of 0.18%, 6 parts of a terminal hydrogen-containing silicone oil having a hydrogen content of 0.18% and 0.1 parts of phenyl butynol were added and stirred for 20 minutes to obtain component B;

[0063] S4. Prepare a thermally conductive gel gasket: evenly mix 100 parts of component A and 100 parts of component B, and cure at 100° C. for 20 minutes to obtain a thermally conductive gel gasket.

[0064] Comparative Example 1

[0065] The difference between Comparative Example 1 and Example 1 is that the base oil is not prepared in advance, and vinyl silicone oil, vinyl silicone resin, fumed silica, hexamethyldisilazane and water are directly added when preparing components A and B.

[0066] Comparative Example 2

[0067] The difference between Comparative Example 2 and Example 1 is that no powder treatment agent is added to components A and B.

[0068] Comparative Example 3

[0069] The difference between Comparative Example 3 and Example 1 is that no modifier is added to component A.

[0070] The addition amount of inorganic material powder in Examples 1-4 is shown in the following table:

[0071] Table 1. Inorganic material powder addition amount in each example

[0072]

[0073] Table 2 Performance test results of the embodiment

[0074]

[0075] In Examples 1-4, thermally conductive gel gaskets are prepared by using two-component liquid silicone rubber. Through special formula design, the thermally conductive gel gaskets prepared have low density and high mechanical properties while meeting the thermal conductivity requirements. The density reaches 1.83 g / cm 3 Compared with conventional thermal pads and conventional two-component thermal gels with a density of 2.2g / cm 3 The above thermal interface materials can better meet the demand for lightweighting and have the ability of low compression permanent deformation. The compression permanent deformation rate is maintained at 30% or below, and the compression strength can be maintained at around 40%. They can be used stably for a long time and have high thermal conductivity and good thermal conductivity.

[0076] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A thermally conductive gel pad, characterized in that: By weight, it includes the following components: Base oil: 98-102 parts of vinyl silicone oil, 5-20 parts of vinyl silicone resin, 15-50 parts of fumed silica, 8-25 parts of hexamethyldisilazane, 5-15 parts of water; Component A: 98-102 parts of base oil, 200-450 parts of inorganic material powder, 0.25-1.5 parts of powder treatment agent, 0.1-1.0 parts of platinum catalyst, and 0.5-2.0 parts of modifier; Component B: 98-102 parts of base oil, 200-450 parts of inorganic material powder, 0.25-1.5 parts of powder treatment agent, 1-12 parts of cross-linking agent, 0.01-0.1 parts of inhibitor; The mass ratio of component A to component B is 1:(0.8-1.2).

2. The thermally conductive gel pad according to claim 1, characterized in that: The vinyl silicone oil is any one of terminal vinyl polydimethylsiloxane and side chain vinyl polydimethylsiloxane.

3. The thermally conductive gel pad according to claim 2, characterized in that: The viscosity of the vinyl silicone oil is 50-500 mPa·s.

4. The thermally conductive gel pad according to claim 1, characterized in that: The vinyl silicone resin is vinyl MQ silicone resin.

5. The thermally conductive gel pad according to claim 1, characterized in that: The inorganic material powder is at least one of zinc oxide with a particle size of 0.1-5 μm, aluminum oxide with a particle size of 1-150 μm, aluminum hydroxide with a particle size of 1-100 μm, aluminum nitride with a particle size of 10-120 μm, or boron nitride with a particle size of 10-200 μm.

6. The thermally conductive gel pad according to claim 1, characterized in that: The powder treatment agent is any one of 3-methacryloxypropyltrimethoxysilane, 8-methacryloxyoctyltrimethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane or hexadecyltrioxymethylsilane.

7. The thermally conductive gel pad according to claim 1, characterized in that: The modifier is any one of benzoyl peroxide and di-tert-butyl peroxide.

8. The thermally conductive gel pad according to claim 1, characterized in that: The crosslinking agent is at least one of a side chain hydrogen-containing silicone oil with a hydrogen content of 0.05%-0.5% or a terminal hydrogen-containing silicone oil with a hydrogen content of 0.05%-0.3%.

9. The method for preparing the thermally conductive gel pad according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Preparation of base oil: Weigh the components of the base oil formula in parts by weight, perform vacuum heat treatment, and obtain a base oil; S2. Preparation of component A: Weigh the base oil and inorganic material powder in step S1 in parts by weight, perform vacuum heat treatment, and then add the powder treatment agent and stir evenly, add the platinum catalyst and the modifier after cooling and stir evenly to obtain component A; S3. Preparation of component B: Weigh the base oil and inorganic material powder in step S1 in parts by weight, perform vacuum heat treatment, and then add the powder treatment agent and stir evenly, add the crosslinking agent and inhibitor and stir evenly after cooling to obtain component B; S4. Component A and component B are mixed according to a mass ratio, and cured at room temperature or at a high temperature of 90° C. to 150° C. for 10 to 30 minutes to obtain the thermally conductive gel gasket.

10. Application of the thermally conductive gel gasket according to any one of claims 1 to 8 in new energy vehicles.